Structural performance of precast floor panel using oil palm shell solid waste - Ng, Cheehiong; Mannan, Mohammad Abdul; Kameswara Rao, N. S V (American Society of Civil Engineers (ASCE), 2016)
The palm oil industry in countries such as Malaysia, Indonesia, and Colombia has been aggressively expanding over the years. Inevitably, the production of palm oil from fresh fruit bunches has generated solid waste, such as oil palm shell (OPS). Such exploitation of OPS when utilized as coarse aggregate in concrete can reduce the reliance of the local construction industry on the use of natural stone aggregates, which are depleting quantitatively. When and if huge amount of OPS can be effectively used, it will not only be a green solution but also a great advantage to both the local palm oil industry and the construction business. Particularly to highlight in typical modern buildings made of reinforced concrete, slab panels consume the most concrete compared to the rest of structural components because they occupy a large space in the floor. Precast floor panels cast with concrete made with OPS can comply with the Industrialized Building System (IBS) because they are innovative, involving the precast system. This paper reports the structural performance of precast floor panels made with OPS concrete under two-line load (TLL), both at the early age of 28 days and a later age of 400 days. Panels tested at an early age failed in a brittle manner, whereas the others, at the later age, failed in a flexural behavior. Results based on parameters, such as service and ultimate load capacity, moment capacity, deflection, cracking characteristics, and ductility, also revealed that the panels performed generally better at a later age compared to an early age. © 2016 American Society of Civil Engineers.